Estrategias financieras de docentes jefes de hogar durante la pandemia COVID-19 - Huayta Supo, Josué (2023)
The purpose of this research is to interpret through an exploratory study how teachers in the rural and urban sectors of the city of Juliaca managed to manage their finances and expenses adequately during the Covid 19 pandemic crisis. In this sense, it was observed how teachers had to adapt to virtual classes and different day-to-day activities and how this change affected their household finances in the context of the pandemic. Therefore, being this context an atypical phenomenon, it was necessary to carry out a qualitative research of phenomenological cut; being that this type of research is based on the experience of the interviewee. The instrument used for data collection was the semi-structured interview; it consisted of 5 questions and these were developed by 5 different iterations to fourteen teachers, 7 from the rural sector and 7 from the urban sector of the city of Juliaca (Southern Region of Peru), after the data collection we proceeded with the analysis of the data, and then to the interpretation of the results. The relevant results during the interviews were that the teachers cover their housing expenses, food, health, mobility and financial commitments through the practice of saving from previous years, which allowed them to subsist in times of economic crisis; in the same way, they cultivate staple products, products of the region satisfying the need for food; the practice of saving through mobilization on foot committed to their income in such a way that they comply with their obligations under the context of the Covid 19 pandemic.